Ciência, construção da nação e exclusão social. São Paulo-Brasil (1889-1930) - Mariza Romero (Les Cahiers ALHIM)
By the end of the Nineteenth century and during the first decades of the Twentieth Century in big Brazilian cities such as São Paulo, there was a great diffusion of hygiene and health patterns which had already been largely adopted in Europe and empowered by scientism, the utmost expression of the progress of science at that time. This scientific progress revealed to the world the existence of a large quantity of germs that seemed to thrive particularly in the bodies of the popular classes, composed by immigrants, black and mixed people – the mestizos – that threatened mainly the ruling class – an elite which should by its very own nature lead the country according to capitalism’s premises. This research aims to understand the practice and action of hygienic physicians in the city of São Paulo, Brazil. According to positivist ideals, this model of activity framed social development on reference to physical sciences model, transforming the theory on evolution in social Darwinism and preaching the superiority of white race over the other ones. It employed Mendel discoveries in order to justify and hinder the proliferation of mestizos, of “degenerated” people, that is, of those who did not fit within the dominant system or resisted against it. On behalf of a neuter and truthful science, popular knowledge was also disqualified, being its owners, the common folks, considered as ignorant people, victim of superstitions. This kind of thinking was meant to guarantee social order, keeping a perfect balance between order and progress, motto of Brazilian national flag.